Interview with Max Presneill, artist, curator and museum director, Los Angeles, 17 September 2017 - Messham-Muir, Kit (StudioCrasher, 2017)
Max Presneill is a Los Angeles-based contemporary artist, curator and museum director. Since our first interview in 2012, I've interviewed Max several times, and her practice is currently the focus of a more in-depth research project looking into studio practice today. In this 360° interview, Max talks about his ongoing exploration into abstraction, and how that relates to the current political situation in the United States. He discusses how moving between abstraction and figuration and back again has expanded his visual language.